2012
DOI: 10.1007/s00262-012-1258-9
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin induces immunogenic cell death in tumor cells and enhances dendritic cell-based cancer vaccine

Abstract: Immunogenic cell death is characterized by damage-associated molecular patterns, which can enhance the maturation and antigen uptake of dendritic cells. Shikonin, an anti-inflammatory and antitumor phytochemical, was exploited here as an adjuvant for dendritic cell-based cancer vaccines via induction of immunogenic cell death. Shikonin can effectively activate both receptor- and mitochondria-mediated apoptosis and increase the expression of all five tested damage-associated molecular patterns in the resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 55 publications
3
122
0
1
Order By: Relevance
“…The substance has been proposed to counteract oxidative stress [1], inflammation [1,2,3], thrombosis [1,2], infections [1,2] and cancer [2,5,6,7,8]. Moreover, Shikonin has been used to support wound healing [1,2,5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substance has been proposed to counteract oxidative stress [1], inflammation [1,2,3], thrombosis [1,2], infections [1,2] and cancer [2,5,6,7,8]. Moreover, Shikonin has been used to support wound healing [1,2,5].…”
Section: Resultsmentioning
confidence: 99%
“…Shikonin has antioxidant [1], anti-inflammatory [1,2,3], antithrombotic [1,2], antiviral [2,4], antimicrobial [1,2], as well as anticancer [2,5,6,7,8] potency and fosters wound healing [1,2,5]. The anticancer effect of Shikonin has been attributed at least in part to the stimulation of suicidal cell death or apoptosis [9,10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant cells are capable of thermotolerance induced by heat-shock response which is accompanied by the expression of HSPs and other post-translational adaptation processes. 109 HT was shown to cause apoptosis mainly at lower temperatures (41)(42)(43) C) (and predominantly necrosis at higher temperatures (>43 C). 110 Increased immunogenicity of mouse and human tumor cells subjected to HT as well as the induction of tumor-antigen specific T cell responses in vitro and in vivo has been well documented.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…109 Clinical HT was shown to affect innate and adaptive immunity; stimulating antigen presentation, maturation and migration of DCs, as well as homing of T lymphocytes to lymph nodes thereby facilitating T cell priming. The efficiency of heat-induced killing of tumor cells depends mainly on the applied temperature (ranging in most studies from 41 C to 44 C), the duration of heat treatment, tumor cell type and the cell cycle phase. Malignant cells are capable of thermotolerance induced by heat-shock response which is accompanied by the expression of HSPs and other post-translational adaptation processes.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Such a DC-based therapeutic approach has been approved by the FDA for the treatment of specific prostate cancers [12]. We and others previously reported that shikonin (SK), a phytochemical derived from the medicinal plant Lithospermum erythrorhizon (LE), can serve as an efficacious adjuvant for expression of damage-associated molecular patterns (DAMPs) and the subsequent induction of ICD in treated carcinoma cells [3, 8]. Moreover, this SK-treated tumor cell lysate (SK-TCL) can be further employed to induce strong in vivo anti-tumor activity for a dendritic cell (DC)-based cancer vaccine [8, 11].…”
Section: Introductionmentioning
confidence: 99%